Effect of leaching pretreatment on the gasification of wine and vine (residue) biomass. (January 2018) - Link, Siim; Arvelakis, Stelios; Paist, Aadu; Liliedahl, Truls; Rosén, Christer
Abstract: Utilization of biomass residues for energetic purposes increases the share of renewables in the total energy balance. Gasification is one of the thermochemical processes that converts solid biomass to valuable gaseous products. Prior to the gasification process, biomass material could be treated to improve the quality or composition of the product gas. Our focus is on fluidized bed gasification of untreated vine and pretreated vine residue and pretreated wine residue. Natural and artificial leaching were used as pretreatment methods. Our results showed that CO and H2 content in the product gas are higher in leached (16.9 and 10.0% respectively) vine residue than in untreated material (14.5 and 7.7% respectively). The naturally leached wine residue was found to have the highest CO content (18.1%) and relatively high H2 content (9.7%) in the product gas, but lower CH4 (1.0%) and CO2 content (5.6%). The results of tar measurements indicated that the leaching pre-treatment lowers the tar content in the evolved product gas, e.g. by 36% in the case of vine residues. As a result, the controlled leaching pretreatment is recommended as an effective way of upgrading the composition of agricultural biomass. Highlights: The leaching affects the composition of producer gas. Artificial/controlled and natural leaching are discussed. Natural leaching increased the content of mineral matter. The effect of mineral matter on gas composition need further studies.